2019
DOI: 10.1016/j.envres.2018.12.059
|View full text |Cite
|
Sign up to set email alerts
|

New approach to identifying proper thresholds for a heat warning system using health risk increments

Abstract: Background: A critical adaptation strategy for reducing heat-related health risk under climate change is to establish a heat warning system with a proper threshold that requires evaluation of heat-health relationships using empirical data. Objectives: This work presents a new approach to selecting proper health-based thresholds for a heat warning system which are different from thresholds of heat-health relationship. Methods: The proposed approach examined heat-health relationships through analyzing 15 years o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
55
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 46 publications
1
55
0
Order By: Relevance
“…Wet-bulb temperatures are a metric that capture the thermodynamic relationship of temperature and humidity and have been applied in the study of weather and human mortality and other human disease. 7,8 These measurements were obtained from National Oceanic and Atmospheric Administration (NOAA) Local Climatological Data.…”
Section: Methodsmentioning
confidence: 99%
“…Wet-bulb temperatures are a metric that capture the thermodynamic relationship of temperature and humidity and have been applied in the study of weather and human mortality and other human disease. 7,8 These measurements were obtained from National Oceanic and Atmospheric Administration (NOAA) Local Climatological Data.…”
Section: Methodsmentioning
confidence: 99%
“…10,11 For this reason, the primary weather variable we used was wet-bulb temperature, a metric that captures the complex thermodynamic relationship of temperature and humidity, has been shown to predict human health events with more precision than temperature and humidity separately, and avoids the associated problem of collinearity. 12,13 Wet-bulb temperatures were obtained from the National Oceanic and Atmospheric Administration Local Climatological Data.…”
Section: Exposuresmentioning
confidence: 99%
“…The tens of thousands of deaths during the heat waves in India and Pakistan in 2015 further revealed that an effective heat warning system is even more critical in developing countries where health care systems lagged behind those in developed countries (7,8). While a heat warning system has long been recognized as the most effective way to reduce heat-related health risks (9,10), the challenge remains in selecting a proper heat indicator and an appropriate threshold with sound scientific evidences (11), which could trigger adequate responsive actions from the authorities to prevent high casualty and advise people for self-protection. This paper aims at providing a systematic approach to assisting authorities worldwide in identifying appropriate heat-warning thresholds.…”
Section: Introductionmentioning
confidence: 99%